2017
DOI: 10.2147/ppa.s116826
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of community-based adherence clubs among health facility staff in South Africa: a qualitative study

Abstract: BackgroundPatient retention in care for HIV/AIDS is a critical challenge for antiretroviral treatment programs. Community-based adherence programs (CBAPs) as compared to health care facility-based adherence programs have been considered as one of the options to provide treatment maintenance support for groups of patients on antiretroviral therapy. Such an approach provides a way of enhancing self-management of the patient’s condition. In addition, CBAPs have been implemented to support antiretroviral treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 18 publications
3
31
1
Order By: Relevance
“…Previous publications have reported concern over stigma in a club setting [26], and some clients did report fears of being recognized by community members when attending the clubs. In contrast to other published data [15], ART stock-outs were not reported as a challenge. ART stock-outs are rare in the Western Cape and it may be that timeous provision of ART is more of a challenge in other settings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous publications have reported concern over stigma in a club setting [26], and some clients did report fears of being recognized by community members when attending the clubs. In contrast to other published data [15], ART stock-outs were not reported as a challenge. ART stock-outs are rare in the Western Cape and it may be that timeous provision of ART is more of a challenge in other settings.…”
Section: Discussioncontrasting
confidence: 99%
“…Perceived advantages of adherence clubs include improved access to services with reduced waiting times, social networking associated with being managed as a group , and an increased role for community healthcare workers (CHWs) . However, healthcare workers have expressed concerns about lack of control of adherence club activities, particularly with respect to provision of ART and other chronic disease medications .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has revealed that males who had long-term housing, living with a partner and belonged to an HIV support group had better antiretroviral adherence (Malta et al, 2010; Wasti et al, 2012). The convenience of picking medication from the community-based adherence clubs leads to a reduction in the numbers of club members sending their friends and family members to pick up the medication this increases interactions with healthcare worker (Tshuma et al, 2017).…”
Section: Social Factors Influencing Health Outcomesmentioning
confidence: 99%
“…Adherence clubs have been implemented to support antiretroviral treatment expansion in resource-limited settings. These clubs involve 30 patients that are allocated to a group and meet at either a facility or a community venue for less than an hour every 2 or 3 months depending on the supply of medication (Bemelmans et Tshuma et al, 2017). For purposes of this study, though particular emphasis will be on patients that are in adherence clubs, we will use any literature that relates to interventions targeted at patients on ART and chronic medication that seek to retain patients in care.…”
Section: Introductionmentioning
confidence: 99%